Neutrophil–Lymphocyte and Platelet–Lymphocyte Ratios as Prognostic Factors after Stereotactic Radiation Therapy for Early-Stage Non–Small-Cell Lung Cancer. Issue 2 (February 2015) - Cannon, Nathan A.; Meyer, Jeffrey; Iyengar, Puneeth; Ahn, Chul; Westover, Kenneth D.; Choy, Hak; Timmerman, Robert
Abstract : Introduction: The hematologic indices of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are correlated with clinical outcomes after stereotactic radiation. Methods: We retrospectively evaluated the pretreatment NLR and PLR in patients treated with stereotactic radiation for early stage non–small-cell lung cancer at our institution. A total of 149 patients treated for non–small-cell lung cancer were identified, and 59 had stage I disease with neutrophil, platelet, and lymphocyte levels within a 3-month period before treatment. Receiver operating characteristic (ROC) analysis was performed to examine cutoff values for survival and nonlocal failure followed by Kaplan–Meier analysis for survival. Results: With a median follow-up of 17 months, 28 deaths were observed, and the median overall survival for all patients was 43 months. Based on the ROC analysis, NLR and PLR cutoff values for further survival analysis were determined based on the ROC analysis to be 2.98 and 146. The median overall survival was not reached for patients with low NLR or PLR but the survival was 23 months for patients with high NLR or PLR. There was no correlation between NLR and nonlocal failure, but on multivariate analysis PLR was found to be associated with freedom from nonlocal failure. Nonlocal failure rates were 11% for patients with PLR less than 250 and 58% for PLR greater than 250 ( p < 0.001). Conclusion: The pretreatment NLR and PLR represented significant prognostic indicators of survival in patients treated for early-stage non–small-cell lung carcinoma with stereotactic radiation. The PLR may be used as a prognostic indicator for nonlocal failure after stereotactic radiation for early-stage lung cancer.